Medieval literature and social politics : studies of cultures and their contexts - Knight, Stephen, 1940- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Medieval Literature and Social Politics brings together seventeen articles by literary historian Stephen Knight. The book primarily focuses on the social and political meaning of medieval literature, in the past and the present. It provides an account of how early heroic texts relate to the issues surrounding leadership and conflict in Wales, France and England, and how the myth of the Grail and the French reworking of Celtic stories relate to contemporary society and its concerns. Further chapters examine Chaucer's readings of his social world, the medieval reworkings of the Arthur and Merlin myths, and the popular social statements in ballads and other literary forms. The concluding chapters examine the Anglo-nationalist `Arctic Arthur', and the ways in which Arthur, Merlin and Robin Hood can be treated in terms of modern studies of the history of emotions and the environment. This book will be of interest to scholars and students of medieval Europe, as well as those interested in social and political history, medieval literature and modern medievalism"--
OCLC-licensed vendor bibliographic record.
Keywords: Literature, Medieval -- History and criticism; Civilization, Medieval, in literature; Literature and society -- Europe -- History; HISTORY / General; LITERARY CRITICISM / European / General; LITERARY CRITICISM / Medieval